2020
DOI: 10.18502/jfqhc.7.2.2887
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fatty Acid Analysis of Frying Oil Using ATR-FTIR Spectroscopy: A Study on Indian Traditional Snack Foods

Abstract: Background: Trans Fatty Acid (TFA) content in oil is an important quality parameter due to its adverse health effect. This study was aimed to examine the TFA content in the frying oil used by street food vendors in India for two traditional snack foods. Methods: Totally, 143 oil samples were collected at different frying times (0, 2, and 4 h) from five different vendors for Samosa and Jalebi. TFA levels of the oil samples were analyzed by Attenuated Total Reflection-Fourier Transform Infrared Spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This may be due to the high moisture content in food that accelerates the hydrolysis reaction [19]. As mentioned in our earlier study [10], this increased TPM might be due to the use of hydrogenated fat by 40 % of the Jalebi vendors and the use of non-hydrogenated fat by the Samosa vendors. Furthermore, a recent study on the influence of fried food and oil type on a dielectric constant based rapid test analysis of TPM in restaurant fried oil concluded that the effect of oil type is more important than the food type to measure TPM using rapid test analysis [20].…”
Section: Total Polar Materials (Tpm)mentioning
confidence: 52%
See 4 more Smart Citations
“…This may be due to the high moisture content in food that accelerates the hydrolysis reaction [19]. As mentioned in our earlier study [10], this increased TPM might be due to the use of hydrogenated fat by 40 % of the Jalebi vendors and the use of non-hydrogenated fat by the Samosa vendors. Furthermore, a recent study on the influence of fried food and oil type on a dielectric constant based rapid test analysis of TPM in restaurant fried oil concluded that the effect of oil type is more important than the food type to measure TPM using rapid test analysis [20].…”
Section: Total Polar Materials (Tpm)mentioning
confidence: 52%
“…The absorption spectra of all the collected samples were obtained by Fourier Transform Infrared (FTIR) Spectrometer (Bruker Optics, Model-Alpha, Germany). The detailed operation method of FTIR was followed as explained in previous articles [10,11]. An OPUS spectroscopy software version 7.2 was used for FTIR data collection and processing.…”
Section: Atr -Ftir Analysismentioning
confidence: 99%
See 3 more Smart Citations